Highly Enhanced Electrocatalytic Performances with Dendritic Bimetallic Palladium-Based Nanocrystals - Respati K. Pramadewandaru (MDPI AG, 2021)
The exploration of efficient nanocatalysts with high activity and stability towards water electrolysis and fuel cell applications is extremely important for the advancement of electrochemical reactions. However, it remains challenging. Controlling the morphology of bimetallic Pd–Pt nanostructures can be a great way to improve their electrocatalytic properties compared with previously developed catalysts. Herein, we synthesize bimetallic Pd–Pt nanodendrites, which consist of a dense matrix of unsaturated coordination atoms and high porosity. The concentration of cetyltrimethylammonium chloride was significant for the morphology and size of the Pd–Pt nanodendrites. Pd–Pt nanodendrites prepared by cetyltrimethylammonium chloride (200 mM) showed higher activities towards both the hydrogen evolution reaction and methanol oxidation reaction compared to their different Pd–Pt nanodendrite counterparts, commercial Pd, and Pt catalysts, which was attributed to numerous unsaturated surface atoms in well-developed single branches.